ANALISIS BIAYA DAN MANFAAT EKOWISATA TAMAN EDEN 100 KECAMATAN LUMBAN JULU KABUPATEN TOBA SAMOSIR PROVINSI SUMATERA UTARA - Valvi Anita Sinaga; Defri Yoza; Tuti Arlita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The existence of the Garden of Eden 100 ecotourism in producing tour benefits intended to achieve an advantage that the management of ecotourism can be done sustainability. In order to the condition of the ownership status of the Garden of Eden 100 held by individual who never made the calculation of costs incurred that are economically not known fee for management of these areas. For that we need to do an analysis of the cost and the benefit of ecotourism Garden of Eden 100.The aimed of this research is to determine the cost of issued, the economical benefit and the advisability of ecotourism business. The results of the research showed that total cost of issued in the  management of ecotourism Garden of Eden 100  in the amount of Rp. 240.740.000,00/year, while total economical benefit from ecotourism in the amount of Rp. 381.670.000,00/year, so that from the benefit it can get advantage in the amount of Rp. 140.930.000,00/year. Analysis of R/C ratio indicates that an ecotourism business deserve economically with a value 1.59.Keywords :ecotourism,ecotourism business, analysis of cost and benefit,the R/C ratio